El reto de la comunicación: liderazgo comunicacional y herramientas negociadoras (Punto de Vista) - Cavallucci de Dalmases, Olga (2017)
This article revolves around two central axes: communication and the art of negotiation as operative elements of communication leadership, which in turn gives rise to a new concept: the “Happy leadership”. The starting point is that every human being has an innate factor and a set of purchasable items, ie, that can be worked through practice and implementation of some tools: Awareness, Behavior, Image, Active listening and empathy.